Financial hedging and corporate investment - Alexandridis, George; Chen, Zhong; Zeng, Yeqin (Journal of Corporate Finance, 2021)
Building on the well-documented relationship between corporate financial hedging and firms' borrowing costs, this study examines the impact of utilizing financial derivative instruments on corporate investment. We document that engaging in financial hedging enables firms to pursue more inorganic growth opportunities in the form of M&As. Acquiring firms with financial hedging programs have a lower borrowing cost and are more likely to pay for their deals with cash and use external borrowing. While financial hedging serves as a vehicle for firms to bring their inorganic investment plans to fruition by facilitating their financing, it also leads to inferior investment choices when conflicts of interest among managers and shareholders are more likely to arise. Our study shows for the first time that the financial flexibility emanating from corporate financial hedging can give rise to agency costs by instigating entrenched managers to overinvest.